Laminate, card, and passport
Patent Information
- Application Number
- JP2023142589
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0009】 本発明によれば、フィルムの廃棄をする必要がなく、ホログラム層に対するダメージを低減可能な積層体を提供することができる。
Smart Images

Figure 2025035505000011 
Figure 2025035505000012 
Figure 2025035505000013
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, a card, and a passport. [Background technology]
[0002] Conventionally, hologram transfer foils have been widely used on cards or passports to transfer hologram images (hereinafter referred to as "holograms" as a general term including relief-type diffraction grating patterns and OVD (Optical Variable Device) patterns) using hot stamping to provide decorative effects and anti-counterfeiting effects (see, for example, Patent Document 1). Hologram transfer foils are generally composed of a substrate, a release layer, a hologram-forming layer, a reflective layer (protective layer), and an adhesive layer, and the substrate and release layer are peeled off at the interface, and the layers following the release layer are transferred to a transferee (e.g., a core sheet) as a transfer layer to form a transfer, and the release layer often functions as a protective layer for the transfer layer. When a PET film is used as the substrate, the PET film is discarded after being peeled off from the release layer, and a separate transparent resin sheet is sometimes attached to protect the hologram-forming layer.
[0003] Incidentally, cards, passports, etc. are generally manufactured by laminating multiple resin films and integrating them by heat pressing. The layer structure may be, for example, a structure in which multiple layers of core sheets are laminated between a pair of oversheets, or a structure in which a laser marking sheet or the like is further provided between the oversheet and the core sheet, and the thickness ratio of the core sheet to the entire product is generally high. This core sheet is required to have a concealing property, and a filler such as titanium oxide is generally blended therein. Furthermore, there is a demand for a laminate having a hologram layer in its layer structure in order to provide decorative effects and anti-counterfeiting effects. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-214172 A Summary of the Invention [Problem to be solved by the invention]
[0005] When manufacturing a laminate having a hologram layer in the layer structure as described above, the hologram transfer foil is used, but when a PET film is used as a substrate, the PET film must be discarded. Furthermore, with regard to the adhesion between the hologram layer and the core sheet, when a polycarbonate resin sheet that has been used for cards, passports, etc. is used as the core sheet, high-temperature pressing at 170°C or higher is required, which causes the hologram layer to yellow. Furthermore, when the hologram layer and the polycarbonate resin sheet are directly bonded without using a PET film, the PET film does not need to be discarded, but the yellowing of the hologram layer due to high-temperature pressing cannot be solved.
[0006] Therefore, an object of the present invention is to provide a laminate that uses a resin sheet of a specific configuration as a constituent unit, thereby eliminating the need to discard the film and reducing damage to the hologram layer. [Means for solving the problem]
[0007] As a result of intensive research, the present inventors have found that the above problems can be solved by combining a hologram layer with a resin sheet made of a resin composition containing a polycarbonate resin having a structural unit derived from a specific dihydroxy compound such as isosorbide, and have completed the present invention as described below. That is, the present invention provides the following items [1] to
[16] .
[0008] [1] A laminate in which a resin sheet A is laminated on one side of a hologram layer, the resin sheet A being made of a resin composition A containing a polycarbonate resin (A) having a structural unit (A1) derived from a dihydroxy compound having a moiety represented by the following formula (1) as part of its structure: [ka] However, this does not include the case where the site represented by formula (1) is a part of -CH2-OH. [2] The laminate according to the above [1], wherein a resin sheet B is laminated on the other surface of the hologram layer, and the resin sheet B is made of a resin composition B containing a polycarbonate resin. [3] The laminate according to the above [2], wherein the resin composition B is a resin composition A containing a polycarbonate resin (A) having a structural unit (A1) derived from a dihydroxy compound having a moiety represented by the following formula (1) as part of its structure: [ka] However, this does not include the case where the site represented by formula (1) is a part of -CH2-OH. [4] The laminate according to any one of the above [1] to [3], wherein the resin composition A constituting the resin sheet A contains an inorganic filler. [5] The laminate according to any one of the above [2] to [4], wherein the resin composition B constituting the resin sheet B contains an inorganic filler. [6] The laminate according to the above [4] or [5], wherein the inorganic filler is a metal oxide. [7] The laminate according to [4] or [5] above, wherein the inorganic filler is titanium oxide. [8] The laminate according to any one of the above [4] to [7], wherein the content of the inorganic filler is 5 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the resin component in each of the resin compositions A and B. [9] The laminate according to any one of the above [2] to [8], wherein the resin composition B constituting the resin sheet B contains a color former.
[10] The laminate according to [9] above, wherein the content of the color former is 0.01 parts by mass or more per 100 parts by mass of the resin component in the resin composition B.
[11] The laminate according to any one of the above [1] to
[10] , wherein the polycarbonate resin (A) contains 30 mol % or more of the structural unit (A1) in structural units derived from a dihydroxy compound.
[12] The laminate according to any one of the above [1] to
[11] , wherein the polycarbonate resin (A) contains 80 mol % or less of the structural unit (A1) in structural units derived from a dihydroxy compound.
[13] The laminate according to any one of the above [1] to
[12] , wherein the polycarbonate resin (A) further contains a structural unit (A2) which is derived from at least one dihydroxy compound selected from the group consisting of an aliphatic dihydroxy compound and an alicyclic dihydroxy compound and is a structural unit other than the structural unit (A1).
[14] The laminate according to any one of the above [1] to
[13] , wherein the hologram layer is of a relief type.
[15] A card or passport having the laminate according to any one of [1] to
[14] above.
[16] The method for producing a laminate according to any one of the above [1] to
[14] , wherein the hologram layer and at least one of the resin sheet A and the resin sheet B are pressed at 160° C. or lower. Effect of the Invention
[0009] According to the present invention, it is possible to provide a laminate that does not require disposal of the film and can reduce damage to the hologram layer. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a conceptual diagram showing a laminate of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing a layer structure of a card. [Diagram 3] FIG. 2 is a schematic diagram showing a layer structure of a card. [Figure 4] FIG. 2 is a schematic diagram showing a layer structure of a card. [Diagram 5] FIG. 2 is a schematic diagram showing a layer structure of a passport. [Figure 6] FIG. 2 is a schematic diagram showing a layer structure of a passport. [Figure 7] FIG. 2 is a schematic diagram showing a layer structure of a passport. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in detail below with reference to the embodiments. However, the present invention is not limited to the embodiments described below. In addition, the terms "film" and "sheet" used in the following description are not clearly distinguished from each other, and the term "film" includes the term "sheet", and the term "sheet" includes the term "film".
[0012] [Laminate] The laminate of the present invention is a laminate in which a resin sheet A is laminated on one side of a hologram layer, and is characterized in that the resin sheet A is made of a resin composition A containing a polycarbonate resin (A) having a structural unit (A1) derived from a dihydroxy compound having a moiety represented by the following formula (1) as part of its structure.
[0013] [ka] However, this does not include the case where the site represented by formula (1) is a part of -CH2-OH.
[0014] By using such a laminate, it is possible to efficiently produce a laminate having a hologram layer, which has been conventionally produced using a transfer foil. More specifically, a laminate, which has been conventionally produced by using a transfer foil composed of a substrate such as PET, a release layer, a hologram-forming layer, a reflective layer (protective layer), and an adhesive layer, peeling at the interface between the substrate and the release layer, transferring the layers subsequent to the release layer to a transferee such as a core sheet or an oversheet, peeling off the substrate, and laminating another transparent resin sheet for protection of the hologram-forming layer, can be produced efficiently by simplifying the process. Moreover, since no base material such as PET is required, no waste material is generated. In addition, by using the resin sheet A, press molding can be performed at a low temperature, so damage to the hologram layer can be reduced.
[0015] The laminate of the present invention will be described below with reference to Fig. 1. In the laminate 100 of the present invention, a resin sheet A (101 in Fig. 1) is laminated on one surface of a hologram layer 102. It is preferable that a resin sheet B is laminated on the other surface of the hologram layer 102. The example shown in Fig. 1 illustrates a structure of resin sheet A (101) / hologram layer (102) / resin sheet B (103-105), and resin sheet B is a three-layer laminate. In the laminate of the present invention, unlike the conventional method in which the base sheet of the transfer foil is peeled off and then another transparent resin sheet is laminated, a release layer is not required between the resin sheet A (101) and the hologram layer (102). However, a release layer may be present as long as it does not impair the effects of the present invention. Moreover, the resin sheet A (101) of the present invention is made of the resin composition A containing the specific polycarbonate resin (A) as described above, and is formed by laminating the resin sheet A (101) and the hologram layer 102. An adhesive layer may or may not be present between the resin sheet A (101) and the hologram layer 102. On the other hand, in order to ensure adhesion between the hologram layer 102 and the resin sheet B (103), an adhesive layer may be provided on the other surface of the hologram layer 102 opposite to the resin sheet A (101).
[0016] <Resin sheet A> Resin sheet A in the laminate of the present invention is made of resin composition A containing polycarbonate resin (A) having a structural unit derived from a dihydroxy compound having a moiety represented by the following formula (1) in part of its structure.
[0017] (Polycarbonate resin (A)) The polycarbonate resin (A) in the present invention has a structural unit (hereinafter sometimes referred to as structural unit (A1)) derived from a dihydroxy compound having a moiety represented by the following formula (1) as part of its structure.
[0018] [ka] However, this does not include the case where the moiety represented by the formula (1) is a part of -CH2-OH. That is, the dihydroxy compound refers to a compound that at least contains two hydroxyl groups and further contains the moiety represented by the formula (1).
[0019] In the present invention, by using the polycarbonate resin (A) having the above structure, the film formed from the resin composition A can be fused at a low temperature during heat press molding, thereby improving the heat press suitability and reducing damage to the hologram layer. Furthermore, as described in detail below, the dihydroxy compound can be obtained using plant-derived substances such as isosorbide as raw materials, and therefore the biomass content of resin composition A, films formed from resin composition A, and final products such as cards and passports containing resin composition A can be improved, thereby reducing the environmental burden. Furthermore, the solvent resistance of the resin composition A is also easily improved.
[0020] The dihydroxy compound having a moiety represented by formula (1) as a part of its structure is not particularly limited as long as it has a structure represented by formula (1) in the molecule. Specific examples of the dihydroxy compound include 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-methylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isopropylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-isobutylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-cyclohexanediyl)fluorene, and the like. Examples of the fluorene include 9,9-bis(4-(2-hydroxyethoxy)-3-phenylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3,5-dimethylphenyl)fluorene, 9,9-bis(4-(2-hydroxyethoxy)-3-tert-butyl-6-methylphenyl)fluorene, and 9,9-bis(4-(3-hydroxy-2,2-dimethylpropoxy)phenyl)fluorene, and compounds having an aromatic group in a side chain and an ether group bonded to the aromatic group in a main chain; and dihydroxy compounds having a cyclic ether structure, such as dihydroxy compounds represented by the following formula (2) and spiroglycol represented by the following formula (3).
[0021] Among the above, dihydroxy compounds having a cyclic ether structure are preferred, and anhydrous sugar alcohols such as those represented by formula (2) are particularly preferred. More specifically, dihydroxy compounds represented by formula (2) include isosorbide, isomannide, and isoidet, which are stereoisomers. In addition, dihydroxy compounds represented by the following formula (3) include 3,9-bis(1,1-dimethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane (common name: spiroglycol), 3,9-bis(1,1-diethyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane, and 3,9-bis(1,1-dipropyl-2-hydroxyethyl)-2,4,8,10-tetraoxaspiro(5.5)undecane. These may be used alone or in combination of two or more.
[0022] [ka]
[0023] [ka] In formula (3), R1 to R4 each independently represent an alkyl group having 1 to 3 carbon atoms.
[0024] The dihydroxy compound represented by the formula (2) is an ether diol that can be produced from carbohydrates using plant-derived substances as raw materials. In particular, isosorbide can be produced inexpensively by hydrogenating and then dehydrating D-glucose obtained from starch, and is abundantly available as a resource. For these reasons, isosorbide is most preferably used.
[0025] The polycarbonate resin (A) may further contain a structural unit other than the structural unit (A1) as a structural unit derived from a dihydroxy compound, and preferably contains, for example, a structural unit derived from at least one dihydroxy compound selected from an aliphatic dihydroxy compound and an alicyclic dihydroxy compound (hereinafter, sometimes referred to as structural unit (A2)).
[0026] The aliphatic dihydroxy compound is not particularly limited with respect to the number of carbon atoms, but preferably includes an aliphatic dihydroxy compound having about 2 to 12 carbon atoms, more preferably 2 to 6 carbon atoms. Specific examples include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 2-ethyl-1,6-hexanediol, 2,2,4-trimethyl-1,6-hexanediol, 1,10-decanediol, 1,12-dodecanediol, hydrogenated dilinoleyl glycol, hydrogenated dioleyl glycol, etc. Preferably, at least one selected from ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol is used, and more preferably, at least one selected from ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol is used. In addition, as the structural unit derived from an aliphatic dihydroxy compound, for example, those described in International Publication No. 2004 / 111106 can also be used.
[0027] The structural unit derived from the alicyclic dihydroxy compound preferably contains at least one of a 5-membered ring structure and a 6-membered ring structure, and in particular the 6-membered ring structure may be fixed to a chair or boat shape by a covalent bond. By containing a structural unit derived from an alicyclic dihydroxy compound of such a structure, the heat resistance of the resulting polycarbonate resin (A) can be improved. The alicyclic dihydroxy compound has, for example, 5 to 70 carbon atoms, preferably 6 to 50 carbon atoms, and more preferably 8 to 30 carbon atoms. The alicyclic dihydroxy compound is preferably at least one selected from cyclohexanedimethanol, tricyclodecane dimethanol, adamantanediol, and pentacyclopentadecanedimethanol, and from the viewpoints of economy and heat resistance, cyclohexanedimethanol or tricyclodecane dimethanol is more preferred, and cyclohexanedimethanol is even more preferred. As for cyclohexanedimethanol, 1,4-cyclohexanedimethanol is particularly preferred from the viewpoint of industrial availability. In addition, as the structural unit derived from an alicyclic dihydroxy compound, those described in WO 2007 / 148604 can also be used.
[0028] The content of the structural unit (A1) in the polycarbonate resin (A) is preferably 30 mol% or more, more preferably 40 mol% or more, even more preferably 45 mol% or more, and also preferably 80 mol% or less, more preferably 75 mol% or less, even more preferably 70 mol% or less, and even more preferably 65 mol% or less, in the structural units derived from the dihydroxy compound. By setting it in such a range, coloring caused by the carbonate structure and coloring caused by impurities contained in trace amounts because of the use of plant resource materials can be effectively suppressed, the transparency of the resin composition can be easily increased, and yellowing can be easily prevented. In addition, it tends to be possible to achieve a suitable balance of physical properties such as moldability, mechanical strength, and heat resistance, which is difficult to achieve with a polycarbonate resin composed only of the structural unit (A1). On the other hand, the content of the structural unit (A2) in the polycarbonate resin (A) in the structural units derived from the dihydroxy compound is preferably 20 mol % or more, more preferably 25 mol % or more, even more preferably 30 mol % or more, still more preferably 35 mol % or more, and is preferably 70 mol % or less, more preferably 60 mol % or less, and even more preferably 55 mol % or less.
[0029] The polycarbonate resin (A) preferably contains a structural unit derived from a dihydroxy compound consisting of a structural unit (A1) and a structural unit (A2), but may contain structural units derived from other dihydroxy compounds as long as the object of the present invention is not impaired. Specifically, a small amount of an aromatic ring-containing dihydroxy compound, such as bisphenol such as 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), may be copolymerized. The use of an aromatic ring-containing dihydroxy compound is expected to efficiently improve heat resistance and moldability, but the incorporation of a large amount of the compound tends to cause problems in weather resistance, so it is recommended to use an amount that does not cause problems in weather resistance. Examples of aromatic ring-containing dihydroxy compounds other than bisphenol A include α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane.
[0030] The glass transition temperature of the polycarbonate resin (A) is, for example, 70° C. or higher, preferably 80° C. or higher, more preferably 85° C. or higher, and even more preferably 90° C. or higher, and, for example, 140° C. or lower, preferably 130° C. or lower, more preferably 125° C. or lower, and even more preferably 120° C. or lower. In addition, it is usually preferable that the polycarbonate resin (A) has a single glass transition temperature. By setting the glass transition temperature within the above range, low-temperature heat fusion property tends to be easily achieved, and further, heat resistance can be easily imparted to the resin composition. The glass transition temperature can be adjusted by appropriately selecting the ratio of each structural unit constituting the polycarbonate resin (A). The glass transition temperature of each resin can be obtained by measurement using a differential scanning calorimeter. The detailed measurement conditions are preferably as described in the examples.
[0031] The polycarbonate resin (A) can be produced by a commonly used polymerization method, and can be produced by either the phosgene method or the transesterification method of reacting with a carbonate diester. Among them, the transesterification method of reacting a dihydroxy compound having a moiety represented by the formula (1) in a part of its structure with another dihydroxy compound with a carbonate diester in the presence of a polymerization catalyst is preferred. The transesterification method is a polymerization method in which a dihydroxy compound, a carbonate diester, a basic catalyst, and an acidic substance for neutralizing the catalyst are mixed to carry out a transesterification reaction. Examples of the carbonic acid diester include diphenyl carbonate, ditolyl carbonate, bis(chlorophenyl) carbonate, m-cresyl carbonate, dinaphthyl carbonate, bis(biphenyl) carbonate, diethyl carbonate, dimethyl carbonate, dibutyl carbonate, and dicyclohexyl carbonate, and among these, diphenyl carbonate is preferably used.
[0032] The molecular weight of the polycarbonate resin (A) can be expressed by a reduced viscosity, and the reduced viscosity is, from the viewpoint of imparting mechanical strength, for example, 0.3 dL / g or more, and preferably 0.35 dL / g or more, and from the viewpoint of increasing fluidity during molding and improving productivity and moldability, for example, 1.2 dL / g or less, preferably 1 dL / g or less, and more preferably 0.8 dL / g or less. The reduced viscosity is measured using dichloromethane as a solvent, the polycarbonate resin concentration is precisely adjusted to 0.6 g / dL, and a temperature of 20.0°C ± 0.1°C is measured using an Ubbelohde viscometer.
[0033] The resin composition A may use only the polycarbonate resin (A) as a resin component, but may contain a resin other than the polycarbonate resin (A) within the scope of the present invention. The resin components constituting the resin composition may contain the polycarbonate resin (A) as a main component, and the polycarbonate resin (A) is, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and most preferably 100% by mass, based on the total amount of the resin components contained in the resin composition.
[0034] <Resin sheet B> It is preferable that a resin sheet B is laminated on the other surface of the hologram layer, i.e., the surface opposite to the surface on which the resin sheet A is laminated. The resin sheet B may be made of a resin composition B containing a polycarbonate resin, and the polycarbonate resin is not particularly limited. That is, a known polycarbonate resin can be used. Therefore, the carbonate resin contained in the resin sheet B may be a bisphenol-based polycarbonate, which will be described later, or the like. Resin composition B may contain the above-mentioned resin composition A, or may be composed of resin composition A alone. In the laminate of the present invention, it is preferable to use the above-mentioned resin composition A as the resin composition B. By using the resin composition A, it is possible to improve the biomass ratio of the final product and reduce the environmental load. In addition, by forming the resin sheet B from the resin composition A, it is possible to fuse the film at a low temperature when hot press molding, and it is possible to improve the hot press suitability and reduce damage to the hologram layer. Resin composition A and resin composition B will be described below, but the term "the resin composition" refers to both resin composition A and resin composition B. The resin composition can be used not only for the resin sheet A and resin sheet B, but also for a core sheet, an overlay sheet, and a laser marking sheet, which will be described later.
[0035] (Inorganic filler) The resin composition may or may not contain an inorganic filler. When used as the resin sheet A or resin sheet B, for example, on the surface side of a laminate, in order to ensure transparency and visibility of the hologram layer, an embodiment can be made in which no inorganic filler is contained or the content of the inorganic filler is low. More specifically, the content of the inorganic filler is preferably less than 10 parts by mass, more preferably less than 8 parts by mass, even more preferably less than 5 parts by mass, and particularly preferably 0 parts by mass, relative to 100 parts by mass of the resin composition. Here, the surface side refers to the surface on the side where the hologram layer is visible. By containing an inorganic filler, the resin composition has low light transmittance and can exhibit, for example, concealment properties. Therefore, the resin composition can be suitably used for cards and passports, and particularly for the core sheet described below. Therefore, it is particularly preferable that the resin composition B constituting the resin sheet B contains an inorganic filler.
[0036] Examples of inorganic fillers include titanium oxide, talc, mica, calcium carbonate, magnesium carbonate, barium oxide, carbon black, silica, lead titanate, potassium titanate, barium titanate, zirconium oxide, magnesium oxide, calcium oxide, aluminum oxide, zinc sulfide, antimony oxide, zinc oxide, boron nitride, aluminum nitride, barium sulfate, etc. Among these, metal oxides are preferable as inorganic fillers.
[0037] Among the above, at least one inorganic filler having a refractive index of 2 or more is preferred, and the refractive index is more preferably 2.2 or more, and even more preferably 2.4 or more. Examples of inorganic fillers having a refractive index of 2 or more include titanium oxide, lead titanate, potassium titanate, barium titanate, zirconium oxide, magnesium oxide, calcium oxide, zinc sulfide, antimony oxide, zinc oxide, aluminum oxide, boron nitride, aluminum nitride, calcium carbonate, magnesium carbonate, and barium sulfate. By using an inorganic filler having a refractive index of 2 or more, the hiding power is further improved, and the filler is easily colored white. From these viewpoints, titanium oxide is more preferred as the inorganic filler. Examples of titanium oxide include, but are not limited to, rutile type titanium oxide and anatase type titanium oxide. The refractive index of the inorganic filler can be measured by the Becke line method.
[0038] The average particle size of the inorganic filler is not particularly limited, but is, for example, 0.01 μm to 1 μm, preferably 0.05 μm to 0.8 μm, more preferably 0.08 μm to 0.6 μm, even more preferably 0.1 μm to 0.5 μm, and still more preferably 0.12 μm to 0.4 μm. The average particle size refers to the average primary particle size observed with a scanning electron microscope.
[0039] The content of the inorganic filler in the present resin composition is preferably 5 parts by mass or more and 90 parts by mass or less with respect to 100 parts by mass of the resin component contained in the present resin composition. By making the content of the inorganic filler 5 parts by mass or more, the concealing property of the film formed from the present resin composition can be improved. In addition, by making the content of the inorganic filler 90 parts by mass or less, it becomes easier to maintain good mechanical properties such as bending resistance. From these viewpoints, the content of the inorganic filler is more preferably 8 parts by mass or more, more preferably 10 parts by mass or more, and when higher concealment is required, more preferably 20 parts by mass or more, more preferably 25 parts by mass or more, more preferably 30 parts by mass or more, and more preferably 35 parts by mass or more. Also, the content of the inorganic filler is more preferably 80 parts by mass or less, more preferably 70 parts by mass or less, more preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and more preferably 45 parts by mass or less, but when higher concealment is not required, it may be 40 parts by mass or less.
[0040] As described above, the inorganic filler is preferably titanium oxide. Therefore, the content of titanium oxide in the resin composition is preferably 5 parts by mass or more and 90 parts by mass or less with respect to 100 parts by mass of the resin component contained in the resin composition. The content of titanium oxide is more preferably 8 parts by mass or more, more preferably 10 parts by mass or more, more preferably 20 parts by mass or more, more preferably 25 parts by mass or more, more preferably 30 parts by mass or more, and more preferably 35 parts by mass or more. The content of titanium oxide is more preferably 80 parts by mass or less, more preferably 70 parts by mass or less, more preferably 60 parts by mass or less, more preferably 50 parts by mass or less, more preferably 45 parts by mass or less, and may be 40 parts by mass or less.
[0041] [Color former] The resin composition may contain a color former. By containing a color former, the resin composition can color the resin sheet formed from the resin composition, making it possible to perform printing and the like. The color former is preferably a laser color former. By containing a laser color former in the resin composition, laser printing is possible on the resin sheet formed from the resin composition. In particular, it is preferable that the resin composition B constituting the resin sheet B contains a color former.
[0042] The laser coloring agent is not particularly limited as long as it has the function of generating heat by irradiation with a laser beam, and may be a so-called self-coloring type coloring agent that generates a color by itself by irradiation with a laser beam, or may be a colorless type coloring agent. When the laser coloring agent generates heat, at least the surrounding forming material is carbonized, and the desired print appears on the resin sheet. Furthermore, when a self-coloring laser coloring agent is used, the coloring of the laser coloring agent and the coloring of the carbonized material generated by carbonizing the forming material of the resin sheet are synergistically combined to produce a print that is dark in color and has excellent visibility. When the laser coloring agent generates a color, the color is not particularly limited, but from the viewpoint of visibility, it is preferable to use a laser coloring agent that can generate a dark color including black, navy blue, and brown.
[0043] The laser coloring agent may be a metal oxide or a compound other than a metal oxide. The metal oxide is not limited as long as it has a laser coloring effect, and examples of the metal oxide include iron oxide, copper oxide, zinc oxide, tin oxide, cobalt oxide, nickel oxide, bismuth oxide, indium oxide, antimony oxide, tungsten oxide, neodymium oxide, mica, hydrotalcite, montmorillonite, and smectite. In addition, examples of laser coloring agents other than metal oxides include metals such as iron, copper, zinc, tin, gold, silver, cobalt, nickel, bismuth, antimony, and aluminum, and their salts such as iron chloride, iron nitrate, iron phosphate, copper chloride, copper nitrate, copper phosphate, zinc chloride, zinc nitrate, zinc phosphate, nickel chloride, nickel nitrate, bismuth subcarbonate, and bismuth nitrate. In addition, metal hydroxides such as magnesium hydroxide, lanthanum hydroxide, nickel hydroxide, and bismuth hydroxide, and metal borides such as zirconium boride, titanium boride, and lanthanum boride can also be used. In addition, as for metal borides, hexaborides have near-infrared absorption ability, and among them, lanthanum hexaboride is preferable because it has excellent laser light absorption efficiency. In addition, dyes and carbon black can also be used. The laser color-developing agent may be used alone or in combination of two or more kinds in the resin composition.
[0044] As the laser coloring agent, it is preferable to use metal oxide from the viewpoint of laser printability. Among them, it is preferable to use bismuth oxide or bismuth-based metal oxide such as metal oxide containing bismuth and at least one metal selected from Zn, Ti, Al, Zr, Sr, Nd and Nb from the viewpoint of laser coloring effect and cost, and it is more preferable to use bismuth oxide. Even with a relatively small amount, bismuth oxide can develop color well, so that the resin sheet can have excellent laser coloring without impairing the transparency.
[0045] The average particle size of the laser coloring agent is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, and particularly preferably 2 μm or less. If the particle size is 10 μm or less, there is no risk of significant reduction in transparency. Here, the particle size means the median diameter (d50) determined by a laser diffraction / scattering method. The average particle size of the laser coloring agent is not limited in terms of the lower limit, but from the viewpoint of printing performance and productivity, it is preferably 0.05 μm or more, more preferably 0.1 μm or more, and even more preferably 0.3 μm or more.
[0046] Examples of commercially available metal oxides include products manufactured by TOMATEC CORPORATION under the trade names "42-903A" and "42-920A" and products manufactured by Merck Performance Materials Co., Ltd. under the trade names "Iriotech 8820" and "Iriotech 8825". When a metal oxide is used as the laser coloring agent, the metal oxide may be used alone, or the metal oxide may be used in combination with a compound other than the metal oxide.
[0047] The content of the laser color former in the resin composition is appropriately set so as to obtain good laser printability. The content of the laser color former is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.03 parts by mass or more, even more preferably 0.06 parts by mass or more, and is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, even more preferably 1 part by mass or less, and particularly preferably 0.8 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin composition.
[0048] When a laser color former other than carbon black is used, the content is as described above. When carbon black is used as the laser color former, the content of the laser color former is not particularly limited, but is preferably 0.0001 part by mass or more, more preferably 0.0005 part by mass or more, even more preferably 0.001 part by mass or more, and is preferably 0.1 part by mass or less, more preferably 0.05 part by mass or less, even more preferably 0.01 part by mass or less, and particularly preferably 0.005 part by mass or less, relative to 100 parts by mass of the resin contained in the resin composition.
[0049] (Impact modifier) The resin composition may contain an impact resistance improver. By containing the impact resistance improver, the resin composition can mitigate the effects of external impacts such as bending and impacts during practical use, and can easily improve the bending durability of films and the like formed from the resin composition. In addition, the resin composition can prevent softening and a decrease in fluidity when heated, and can easily maintain good processability.
[0050] Examples of the impact resistance improver include soft styrene-based resins and elastomers. The elastomer may be a core-shell type elastomer. The impact resistance improver may be used alone or in combination of two or more types. Among the above, the core-shell type elastomer is preferred as the impact resistance improver. By using the core-shell type elastomer, the impact resistance is further improved and the bending durability is further improved.
[0051] Examples of the soft styrene-based resin include a block copolymer containing a styrene polymer block and a conjugated diene polymer block, and a block copolymer containing a styrene polymer block and an acrylonitrile block. The styrene content in the soft styrene-based resin is, for example, 5% by mass or more and 80% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. By having the styrene content in the above range, the effect of imparting impact resistance is further improved.
[0052] As the conjugated diene polymer block used in the soft styrene-based resin, a homopolymer of butadiene, isoprene, 1,3-pentadiene, or the like, a copolymer thereof, or a copolymer containing a monomer copolymerizable with the conjugated diene monomer in the block, or the like can be used. Specific examples of soft styrene resins include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), silicone-acrylic composite rubber-acrylonitrile-styrene copolymers (SAS), methyl methacrylate-maleic anhydride-styrene copolymers (SMM), acrylonitrile-styrene copolymers (AS), acrylonitrile-butadiene-styrene copolymers (ABS), acrylonitrile-styrene-acrylic rubber copolymers (ASA), acrylonitrile-ethylene propylene rubber-styrene copolymers (AES), etc. Specific examples of products include the "Kraton D" series manufactured by Kraton Polymers, the "AR-100" series manufactured by Aronkasei, the "Dialac" series manufactured by UMG ABS, and the "Delpet" series manufactured by Asahi Kasei Chemicals. As the soft styrene-based resin, the styrene-based elastomer described below, such as the "Dynaron" series manufactured by JSR Corporation, the "Tuftech" series manufactured by Asahi Kasei Chemicals Corporation, and the "Hybler" series manufactured by Kuraray Co., Ltd. can also be used.
[0053] Block copolymers include pure blocks, random blocks, tapered blocks, etc., and there is no particular restriction on the form of copolymerization. The block units may also have multiple repeating units. Specifically, in the case of styrene-butadiene block copolymers, the block units may be repeated multiple times, such as styrene-butadiene copolymers, styrene-butadiene-styrene block copolymers, and styrene-butadiene-styrene-butadiene block copolymers.
[0054] Hydrogenated styrene-butadiene-styrene block copolymers (SEBS) and hydrogenated styrene-isoprene-styrene block copolymers (SEPS), in which some or all of the double bonds in the conjugated diene polymer blocks of SBS and SIS are hydrogenated, can also be used. Specific examples of such products include the "Tuftech H" series manufactured by Asahi Kasei Chemicals Corporation and the "Kraton G" series manufactured by Kraton Polymers.
[0055] A functional group having polarity can be added to the soft styrene-based resin. Specific examples of the functional group having polarity include an acid anhydride group, a carboxylic acid group, a carboxylic acid ester group, a carboxylic acid chloride group, a carboxylic acid amide group, a carboxylate group, a sulfonic acid group, a sulfonic acid ester group, a sulfonic acid chloride group, a sulfonic acid amide group, a sulfonate group, an epoxy group, an amino group, an imide group, and an oxazoline group. Among these, it is preferable to add an acid anhydride group or an epoxy group. As the soft styrene-based resin to which a polar functional group is added, modified products of SEBS and SEPS are preferably used. Specific examples include maleic anhydride-modified SEBS, maleic anhydride-modified SEPS, epoxy-modified SEBS, and epoxy-modified SEPS. Specific commercial products include the "Tuftec M" series manufactured by Asahi Kasei Chemicals Corporation, the "Dynaron" series manufactured by JSR Corporation, and the "Epofriend" series manufactured by Daicel Chemical Industries, Ltd.
[0056] The soft styrene-based resin may be a styrene-based elastomer containing an elastomer component. Specifically, among the above, there may be mentioned block copolymers of a styrene component and butadiene, isoprene, 1,3-pentadiene, etc., and modified products or hydrogenated products thereof may also be used. More specifically, there may be mentioned SBS, SIS, SEBS, SEPS, etc.
[0057] The elastomer may be other than the styrene-based elastomer, and examples thereof include known elastomers such as polyester-based elastomers, polyolefin-based elastomers, diene-based elastomers, acrylic-based elastomers, polyamide-based elastomers, polyurethane-based elastomers, fluorine-based elastomers, and silicone-based elastomers. The elastomer is generally a thermoplastic elastomer. The elastomer is preferably a polyester-based elastomer or the above-mentioned styrene-based elastomer.
[0058] The polyester elastomer is a thermoplastic polyester having rubber properties at room temperature, preferably a thermoplastic elastomer mainly composed of a polyester block copolymer, and is preferably a block copolymer having a high melting point and high crystallinity aromatic polyester as a hard segment and an amorphous polyester or amorphous polyether as a soft segment. The content of the soft segment of the polyester elastomer is at least 20 to 95 mol% of the total segments, and in the case of a block copolymer of polybutylene terephthalate and polytetramethylene glycol (PTMG-PBT copolymer), it is 50 to 95 mol%. The preferred content of the soft segment is 50 to 90 mol%, particularly 60 to 85 mol%. Among them, a polyester ether block copolymer, particularly a PTMG-PBT copolymer, is preferred.
[0059] The core-shell elastomer is composed of an innermost layer (i.e., a core) and one or more outer layers (i.e., shells) covering the innermost layer. The core-shell elastomer is preferably a core-shell graft copolymer in which a monomer component capable of being graft-copolymerized with the core is graft-copolymerized as the shell.
[0060] The core-shell type graft copolymer has a polymer component called a rubber component as the core. In the core-shell type graft copolymer, it is preferable that the polymer component constituting the core and a monomer component copolymerizable with this polymer component are graft-copolymerized as the shell. The core-shell graft copolymer may be produced by any of the following methods: bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. The copolymerization method may be either one-stage grafting or multi-stage grafting. However, commercially available core-shell elastomers can usually be used as they are. Examples of commercially available core-shell elastomers are given later.
[0061] Specific examples of the polymer component forming the core include butadiene-based rubbers such as polybutadiene and styrene-butadiene copolymers, isoprene-based rubbers, acrylic rubbers such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymers, silicone-based rubbers such as polyorganosiloxane rubber, butadiene-acrylic composite rubbers, silicone-acrylic composite rubbers such as IPN (Interpenetrating Polymer Network) composite rubbers consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, ethylene-α-olefin-based rubbers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers, ethylene-acrylic rubbers, and fluororubbers. These may be used alone or in combination of two or more. Among these, at least one selected from butadiene-based rubbers, acrylic rubbers, silicone-based rubbers, and silicone-acrylic composite rubbers is preferred from the standpoint of mechanical properties and surface appearance, and at least one selected from butadiene-based rubbers and silicone-acrylic composite rubbers is more preferred.
[0062] Specific examples of the monomer component constituting the shell and capable of graft copolymerization with the polymer component of the core include aromatic vinyl compounds; vinyl cyanide compounds; (meth)acrylic compounds such as (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, and epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, aromatic vinyl compounds, vinyl cyanide compounds, and (meth)acrylic compounds are preferred from the standpoint of mechanical properties and surface appearance, and more preferably aromatic vinyl compounds, (meth)acrylic compounds, and especially (meth)acrylic acid ester compounds. Specific examples of aromatic vinyl compounds include styrene, α-methylstyrene, 1-vinylnaphthalene, 4-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, and halogenated styrenes. Of these, styrene and α-methylstyrene are more preferred. Specific examples of the (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate, and among these, methyl (meth)acrylate and ethyl (meth)acrylate, which are relatively easily available, are preferred, and methyl (meth)acrylate is more preferred. Note that "(meth)acrylic" is a general term for "acrylic" and "methacrylic".
[0063] As the core-shell type elastomer, a core-shell type graft copolymer is particularly preferred, which is composed of a core made of at least one polymer component selected from butadiene rubber, acrylic rubber, silicone rubber, and silicone-acrylic composite rubber, and a shell formed by graft copolymerizing a (meth)acrylic compound such as a (meth)acrylic acid ester or an aromatic vinyl compound around the core. The content of the polymer component in the core in the core-shell type graft copolymer is preferably 40% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The total content of the (meth)acrylic compound (particularly, the (meth)acrylic acid ester) component and the aromatic vinyl compound component in the shell of the core-shell type graft copolymer is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 70% by mass or more. In the shell, either the (meth)acrylic compound or the aromatic vinyl compound may be used alone, or these may be used in combination.
[0064] Preferred specific examples of the core-shell type elastomer include methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic-butadiene rubber copolymer, methyl methacrylate-acrylic-butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic-silicone composite rubber) copolymer, and the like.
[0065] Commercially available core-shell type graft copolymers include, for example, "PARALOID EXL2602", "PARALOID EXL2603", "PARALOID EXL2690", "PARALOID EXL2691J", "PARALOID EXL2650J", "PARALOID EXL2655", "PARALOID EXL2311", "PARALOID EXL2313", "PARALOID EXL2315", "PARALOID KM330", "PARALOID KM336P", and "PARALOID KCZ201" manufactured by Dow Chemical Japan Co., Ltd.; Examples of such compounds include "Metabrene C-223A", "Metabrene E-901", "Metabrene S-2001", "Metabrene W-450A", "Metabrene SRK-200", "Metabrene E-870A", "Metabrene S-2006", "Metabrene W-377", and Kaneka Corporation's "Kane Ace M-210", "Kane Ace M-511", "Kane Ace M-600", "Kane Ace M-400", "Kane Ace M-580", "Kane Ace M-590", "Kane Ace M-711", "Kane Ace MR-01", and "Kane Ace M-300". These impact resistance improvers such as core-shell type graft copolymers may be used alone or in combination of two or more kinds.
[0066] The content of the impact modifier in the resin composition is preferably 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the resin component contained in the resin composition. When the content of the impact modifier is 1 part by mass or more, the influence caused by external impact is moderately alleviated, and bending durability and the like are likely to be improved. In addition, the softening property and fluidity of the resin composition when heated, which are caused by the type of resin used, are prevented from decreasing, and the processability is likely to be maintained well. On the other hand, by making the content 30 parts by mass or less, an effect commensurate with the content can be exhibited. In addition, various physical properties such as heat resistance, moist heat resistance, and mechanical strength of the resin composition can be prevented from decreasing. Furthermore, depending on the type of resin in the resin composition, the biomass degree can be reduced, and the fluidity of the resin composition during processing can be prevented from becoming too high. The content of the impact modifier in the present resin composition is more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, and more preferably 25 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less.
[0067] (Other resin components) The resin composition may contain resin components other than the polycarbonate resin (A) (also referred to as "other resin components"). As such resin components, it is preferable to use known resins that are widely used, and it is preferable to use resins that are compatible with the polycarbonate resin (A). The other resin components may be any resin other than the polycarbonate resin (A) and impact resistance improver described above, and among these, thermoplastic resins are preferred. Examples of such resins include polycarbonate resins other than the polycarbonate resin (A) described above, polyester resins, polyolefin resins, acrylic resins, polystyrene resins, polyamide resins, polyvinyl chloride resins, polyvinylidene chloride resins, polyvinyl alcohol resins, ethylene-vinyl alcohol resins, polycycloolefin resins, ethylene-vinyl acetate copolymer resins, ethylene (meth)acrylate copolymer resins, polyphenylene ether resins, polyacetal resins, acrylonitrile-butadiene-styrene copolymer resins, polyaryl ether ketone resins, polyimide resins, polyphenylene sulfide resins, polyarylate resins, polysulfone resins, polyether sulfone resins, and fluororesins. Among these, polycarbonate resins other than the polycarbonate resin (A) and polyester resins are preferred. By using a polycarbonate resin, bending durability is improved and heat resistance and other properties are easily improved. In the following description, the polycarbonate resin other than the polycarbonate resin (A) may be referred to as a polycarbonate resin (B). Moreover, the resin composition B contains a known polycarbonate resin, and also includes the following polycarbonate resin (B).
[0068] (Polycarbonate resin (B)) As the polycarbonate resin (B), a polycarbonate resin other than the polycarbonate resin (A) having the above-mentioned structural unit (A1) may be used, but it is preferable to use a bisphenol-based polycarbonate. By using a bisphenol-based polycarbonate, various mechanical properties become good, and the bending durability described above is also easily improved. In addition, it is easy to make the heat resistance and the like excellent.
[0069] Bisphenol-based polycarbonate refers to a structural unit derived from a dihydroxy compound, in which 50 mol% or more, preferably 70 mol% or more, more preferably 90 mol% or more of the structural unit is derived from bisphenol. The bisphenol-based polycarbonate may be either a homopolymer or a copolymer. In addition, the bisphenol-based polycarbonate may have a branched structure or a straight-chain structure, or may be a mixture of a resin having a branched structure and a resin having only a straight-chain structure.
[0070] Specific examples of bisphenols used in the polycarbonate resin (B) include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)-1-phenylethane (bisphenol AP), 2,2-bis(4-hydroxyphenyl)hexafluoropropane (bisphenol AF), 2,2-bis(4-hydroxyphenyl)butane (bisphenol B), bis(4-hydroxyphenyl)diphenylmethane (bisphenol BP), 2,2-bis(3-methyl-4-hydroxyphenyl)propane (bisphenol C), 1,1-bis(4-hydroxyphenyl)ethane (bisphenol E), bis(4-hydroxyphenyl)methane (bisphenol F). ), 2,2-bis(4-hydroxy-3-isopropylphenyl)propane (bisphenol G), 1,3-bis(2-(4-hydroxyphenyl)-2-propyl)benzene (bisphenol M), bis(4-hydroxyphenyl)sulfone (bisphenol S), 1,4-bis(2-(4-hydroxyphenyl)-2-propyl)benzene (bisphenol P), 5,5'-(1-methylethylidene)-bis[1,1'-(bisphenyl)-2-ol]propane (bisphenol PH), 1,1-bis(4-hydroxyphenyl)3,3,5-trimethylcyclohexane (bisphenol TMC), and 1,1-bis(4-hydroxyphenyl)cyclohexane (bisphenol Z). Bisphenols may be used alone or in combination of two or more.
[0071] As the bisphenol used in the polycarbonate resin (B), 2,2-bis(4-hydroxyphenyl)propane, i.e., bisphenol A, is preferably used, but a part of bisphenol A may be replaced with another bisphenol. As the polycarbonate resin (B), bisphenol A homopolycarbonate is most preferable.
[0072] (polyester resin) The polyester resin used as the resin component may be a polyester obtained by polycondensation of a dicarboxylic acid and a dihydroxy compound. As the dicarboxylic acid, a dicarboxylic acid derivative such as an ester or an acid halide of a dicarboxylic acid may be used for synthesis of the polyester resin. When a polyester resin is used as the resin, the low-temperature fusion property is improved, and a film formed from the resin composition is easily bonded to another film by heat fusion at a relatively low temperature. In addition, the processability is easily improved.
[0073] As the dicarboxylic acid used to obtain the polyester resin, it is preferable to use an aromatic dicarboxylic acid from the viewpoint of heat resistance, and therefore the polyester resin preferably contains structural units derived from an aromatic dicarboxylic acid. The aromatic dicarboxylic acid is not particularly limited, and examples thereof include terephthalic acid, isophthalic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, anthracene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-sulfoisophthalic acid, sodium 3-sulfoisophthalate, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, 2-methylterephthalic acid, and the like. Of these, terephthalic acid and isophthalic acid are preferred, and terephthalic acid is more preferred. The aromatic dicarboxylic acids may be used alone or in combination of two or more.
[0074] The aromatic dicarboxylic acid-derived structural units are preferably contained in the polyester resin in an amount of, for example, 60 mol % or more, preferably 70 mol % or more, more preferably 80 mol % or more, and even more preferably 90 mol % or more of the dicarboxylic acid-derived structural units. The upper limit is not particularly limited as long as it is 100 mol % or less, and is most preferably 100 mol %.
[0075] In addition to the structural units derived from aromatic dicarboxylic acids, the polyester resin may contain a small amount (usually 40 mol% or less, for example 30 mol% or less, preferably 20 mol% or less) of structural units derived from aliphatic dicarboxylic acids. The aliphatic dicarboxylic acids are not particularly limited, and examples thereof include oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, azelaic acid, dodecanedioic acid, dimer acid, 1,3 or 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, and 4,4'-dicyclohexyldicarboxylic acid. The aliphatic dicarboxylic acids may be used alone or in combination of two or more.
[0076] The polyester resin preferably contains a structural unit derived from a chain dihydroxy compound. By containing a structural unit derived from a chain dihydroxy compound, the low-temperature fusion property of the resin composition of the present invention tends to be good. The chain dihydroxy compound used in the polyester resin may be linear or may have a branched structure. Specific examples of the chain dihydroxy compound include chain dihydroxy compounds having about 2 to 18 carbon atoms, such as ethylene glycol (EG), diethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, triethylene glycol, 1,2-hexadecanediol, and 1,18-octadecanediol, and polyglycols, such as polytetramethylene ether glycol, polypropylene glycol, and polyethylene glycol. Among these, a chain dihydroxy compound having 2 to 12 carbon atoms is preferred, and one or more selected from ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol are more preferred, with ethylene glycol (EG) being particularly preferred. The chain dihydroxy compound may be used alone or in combination of two or more kinds.
[0077] The polyester resin is preferably a copolymer polyester resin using two or more dihydroxy compounds as copolymerization components. Specifically, it is preferable to use an alicyclic dihydroxy compound in addition to a chain dihydroxy compound as the dihydroxy compound used to obtain the polyester resin. Therefore, it is preferable that the polyester resin has a structural unit derived from an alicyclic dihydroxy compound in addition to a structural unit derived from a chain dihydroxy compound. By using an alicyclic dihydroxy compound, the heat resistance, solvent resistance, etc. are easily improved. Specific examples of alicyclic dihydroxy compounds include tetramethylcyclobutanediol, cyclohexanedimethanol (CHDM), tricyclodecane dimethanol, adamantanediol, and pentacyclopentadecanedimethanol. Among these, tetramethylcyclobutanediol and cyclohexanedimethanol are preferred. Cyclohexanedimethanol includes 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol is preferred because it is easily available industrially. In addition, 2,2,4,4-tetramethyl-1,3-cyclobutanediol is generally used as tetramethylcyclobutanediol. The alicyclic dihydroxy compound may be used alone or in combination of two or more. As the alicyclic dihydroxy compound, it is preferable to use at least cyclohexanedimethanol, and from the viewpoint of bending resistance, it is preferable to use tetramethylcyclobutanediol and cyclohexanedimethanol in combination.
[0078] In the polyester resin, the ratio of the structural unit derived from the alicyclic dihydroxy compound is, for example, 5 mol% or more, preferably 15 mol% or more, more preferably 20 mol% or more, and for example, 99 mol% or less, preferably 95 mol% or less, more preferably 90 mol% or less, and even more preferably 80 mol% or less, out of the total 100 mol% of the structural unit derived from the chain dihydroxy compound and the structural unit derived from the alicyclic dihydroxy compound. By containing a certain amount or more of the structural unit derived from the alicyclic dihydroxy compound, the polyester resin is likely to have good heat resistance. In addition, by containing a certain amount or less of the structural unit derived from the alicyclic dihydroxy compound and a certain amount or more of the structural unit derived from the chain dihydroxy compound, the low-temperature fusion property is likely to be good.
[0079] In terms of low-temperature fusion properties, the proportion of structural units derived from alicyclic dihydroxy compounds in the total of 100 mol % of structural units derived from chain dihydroxy compounds and structural units derived from alicyclic dihydroxy compounds is preferably 65 mol % or less, more preferably 55 mol % or less, even more preferably 45 mol % or less, and even more preferably 40 mol % or less. However, in terms of heat resistance and solvent resistance, particularly in terms of storage modulus and thermal expansion / contraction rate under high temperature environments, the polyester resin preferably contains structural units derived from alicyclic dihydroxy compounds in a total of 100 mol % of structural units derived from chain dihydroxy compounds and structural units derived from alicyclic dihydroxy compounds, and the proportion of such structural units is preferably more than 65 mol %, more preferably 70 mol % or more, even more preferably 80 mol % or more, and still more preferably 90 mol % or more.
[0080] As the dihydroxy compound used in the polyester resin, dihydroxy compounds other than chain dihydroxy compounds and alicyclic dihydroxy compounds (also referred to as "other dihydroxy compounds") may be used within the scope of not impairing the effects of the present invention. In the polyester resin, the content of structural units derived from other dihydroxy compounds is, for example, 20 mol% or less, preferably 10 mol% or less, more preferably 5 mol% or less, and most preferably 0 mol% in 100 mol of structural units derived from dihydroxy compounds in the polyester resin. Other dihydroxy compounds include p-xylenediol, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), tetrabromobisphenol A, tetrabromobisphenol A-bis(2-hydroxyethyl ether), α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane.
[0081] Of the above, from the viewpoints of low-temperature fusion property, heat resistance, solvent resistance, and the like, the polyester resin preferably contains a structural unit derived from ethylene glycol and a structural unit derived from cyclohexanedimethanol, and also preferably contains a structural unit derived from ethylene glycol, a structural unit derived from cyclohexanedimethanol, and a structural unit derived from tetramethylcyclobutanediol.
[0082] The polyester resin is preferably an amorphous polyester. By using an amorphous polyester, the adhesiveness of the film formed from the resin composition to other members such as a resin film tends to be good. The amorphous polyester may be a polyester that is substantially amorphous. As the substantially amorphous (including low crystalline) polyester, a polyester that does not show a clear crystalline melting peak when heated by a differential scanning calorimeter (DSC), a polyester that has crystallinity but has a slow crystallization rate and does not become highly crystalline when molded by an extrusion film forming method, or a crystalline polyester that has a low crystalline melting heat (ΔHm) of 10 J / g or less when heated by a differential scanning calorimeter (DSC) can be used. That is, the amorphous and polyester in the present invention also include "crystalline polyester in an amorphous state".
[0083] The present resin composition may contain components other than the resin component, filler, color former, impact resistance improver, and ionic acid generator, for example, additives other than these (also referred to as other additives).
[0084] Specific examples of other additives include antioxidants, heat stabilizers, process stabilizers, ultraviolet absorbers, light stabilizers, matting agents, processing aids, metal deactivators, residual polymerization catalyst deactivators, antibacterial and antifungal agents, antiviral agents, antistatic agents, lubricants, flame retardants, pigments, dyes, and other colorants, which are generally used in a wide range of resin materials. These additives may be added in amounts generally used depending on the purpose of use. These additives may be used alone or in combination of two or more.
[0085] The resin composition may be obtained by mixing raw materials constituting the resin composition, such as polycarbonate resin (A), and fillers, color formers, impact absorbing agents, other additives, and resin components other than polycarbonate resin (A) that are blended as necessary. The raw materials may be mixed by melt kneading while heating in an extruder, a plastomill, or the like. The temperature during kneading is, for example, 180°C or higher and 320°C or lower, preferably 200°C or higher and 310°C or lower, and more preferably 220°C or higher and 300°C or lower.
[0086] The resin sheet A may have a single layer structure or a multilayer structure. The number of layers of the multilayer resin sheet A is not particularly limited as long as it has two or more resin layers. The multilayer resin sheet A may have each resin layer made of the present resin composition. The resin compositions constituting each resin layer of the multilayer resin sheet A may be the same or different from each other. Similarly to the resin sheet A, the resin sheet B may have a single layer structure or a multilayer structure. The number of layers of the multilayer resin sheet B is not particularly limited as long as it has two or more resin layers. The resin layer of the multilayer resin sheet B may be composed of the present resin composition or may be composed of another resin composition. The resin composition constituting each resin layer of the multilayer resin sheet B may be the same or different from each other.
[0087] The thickness of the resin sheet A and the resin sheet B is not particularly limited and may be appropriately adjusted depending on the purpose of use, but is, for example, 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and even more preferably 40 μm or more, and is, for example, 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less, even more preferably 250 μm or less, and even more preferably 200 μm or less. By making the thickness of the present film a certain level or more, the present film is more likely to exhibit appropriate functions. For example, when an inorganic filler is contained, it is easier to ensure concealment. On the other hand, by making the thickness below a certain level, it is easier to make cards and passports thinner.
[0088] (Method of manufacturing resin sheet A and resin sheet B) The resin sheet A and the resin sheet B can be produced by a known method, but it is preferable to obtain the resin composition for forming the resin sheet A and the resin sheet B as described above and form the resin composition into a film. The method for forming the resin composition into a film is not particularly limited, and may be press molding or extrusion molding, although extrusion molding is preferred from the standpoint of productivity and cost.
[0089] In addition, when the resin sheet has a multi-layer structure, a resin composition for forming each layer may be prepared, and each resin layer may be formed from each resin composition while laminating a plurality of resin layers by a known lamination method. Also, a composition for forming another resin layer may be melt-extruded and laminated on a resin layer formed from any of the resin compositions. A multi-layer structure may also be formed by co-extrusion. From the viewpoints of productivity, cost, etc., it is preferable to adopt a co-extrusion method. In the laminated film, the resin composition for forming each layer may be obtained by mixing the components for forming each layer according to the composition of each layer.
[0090] (Hologram layer) The hologram layer may be a volume hologram layer or a relief hologram layer, either of which may be used in the present invention, but the relief type is preferred from the viewpoint of ease of manufacture. The relief type hologram layer will be described in detail below. The relief type hologram layer may be any layer having a surface with a concave-convex structure (relief structure) corresponding to interference fringes, and any known layer may be used. Specifically, a desired fine concave-convex pattern is formed by using a photocurable resin, a thermosetting resin, or a thermoplastic resin and then curing the resin.
[0091] When a photocurable resin is used for the hologram layer, the refractive index of the cured resin is about 1.5. In addition, photocurable resin is less likely to cause deformation of the fine uneven pattern shape, and the visibility of the hologram image is improved. The thickness of the hologram layer is preferably within the range of 0.8 μm to 1.5 μm. If the thickness is 0.8 μm or more, the heat resistance of the hologram layer is good, and if the thickness is 1.5 μm or less, the fine concave-convex pattern is maintained.
[0092] Photocurable resins are primarily composed of reactive diluents such as monofunctional or polyfunctional acrylates, oligomers such as epoxy acrylates, urethane acrylates, and polyester acrylates, photopolymerization initiators such as benzophenones, acetophenones, and thioxanthones, and photopolymerization accelerators such as tertiary amines. When the uncured coating surface of a photocurable resin is irradiated with light, the methacryloyl groups at the terminals undergo a radical polymerization reaction, crosslinking and curing. In addition, strong intermolecular forces due to hydrogen bonds between the hydroxyl groups in the molecules act, resulting in a hard, heat-resistant cured product after irradiation.
[0093] Examples of thermosetting resins that can be used include epoxy resins having epoxy groups, epoxy resins or acrylic resins crosslinked by adding polyamide to (meth)acrylates having glycidyl groups, urethane resins crosslinked by adding polyisocyanate or polyamide to acrylic polyols or polyester polyols having reactive hydroxyl groups, melamine resins, and phenolic resins. Suitable thermoplastic resins include acrylic resins, epoxy resins, cellulose resins, vinyl resins, etc., such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, nitrocellulose, polyethylene (PE), polypropylene (PP), acrylic styrene copolymer (AS), vinyl chloride, polymethyl methacrylate (PMMA), etc.
[0094] A relief (unevenness) is formed on the surface of the hologram layer, and a reflective layer is formed on the surface of the relief to improve visibility. The reflective layer can be made of a transparent coating material, a metal coating material, or the like. When a transparent film material is used as the material for the reflective layer, a refractive index difference between the hologram layer and the reflective layer is necessary. The refractive index difference between the hologram layer and the reflective layer is preferably 0.5 or more. When the refractive index difference is 0.5 or more, a sufficient visual effect of diffracted light due to the fine uneven pattern formed on the hologram layer can be obtained. From the above points, it is more preferable to use ZnS, TiO2, PbTiO2, ZrO, ZnTe, PbCrO4, etc., which have a refractive index of 2.0 or more as the transparent material. The thickness of the reflective layer is preferably within the range of 50 nm to 100 nm. When the thickness of the reflective layer is 50 nm or more, the light is reflected evenly and a sufficient visual effect can be obtained.
[0095] When a metal film material is used as the material of the reflective layer, it is possible to use a single material selected from chromium, nickel, aluminum, iron, titanium, silver, gold, and copper, or a mixture, alloy, etc. of these. The thickness of the reflective layer is preferably within the range of 50 nm to 100 nm.
[0096] The reflective layer is preferably formed by vacuum deposition techniques such as vacuum deposition and sputtering. The reflective layer may be formed on the entire surface of the hologram layer on which the relief is formed, or may be formed by patterning.
[0097] In addition, a substrate may be present on the surface of the hologram layer 102 facing the resin sheet A (101). That is, when the hologram layer is provided on a substrate, the substrate and the resin sheet A are bonded together by heat pressing or the like to obtain the laminate of the present invention. Suitable examples of the resin used for the substrate include polyester resins, etc. As the polyester resin, the polyester resin usable in the resin sheet A and the polyester resin usable in the sheet B may be used, or PET (polyethylene terephthalate), PEN (polyethylene naphthalate), etc. may be used.
[0098] An adhesive layer (not shown) may be provided on the surface of hologram layer 102 facing resin sheet B, if necessary. When a resin sheet made of resin composition A is used as resin sheet B and hologram layer 12 and resin sheet B (103 to 105) are directly bonded, this is not necessarily required; however, when resin sheet B uses a resin other than resin composition A or when resin sheet B is bonded to a resin sheet other than resin sheet B, it is preferable for resin sheet B to have an adhesive layer. The surface of the hologram layer 102 facing the resin sheet A may also have an adhesive layer (not shown) as necessary. In addition, resin sheet A / hologram layer is first adhered, and then another resin sheet (eg, resin sheet B) is heat-pressed therewith. Since no peeling step is involved as in the conventional method, this method has the advantage that pressing can be done in one go. As described above, when pressing in one go, the hologram may be aligned by combining a method known as normal alignment, such as register printing or punching holes in the sheet to which the hologram layer is transferred. The material constituting the adhesive layer is not particularly limited as long as it has adhesion to other resins, and examples of the material that can be used include thermoplastic resins such as polypropylene resin, polyethylene terephthalate resin, polyacetal resin, polyester resin, etc. The material of the adhesive layer may contain an inorganic material such as silica. The thickness of the adhesive layer is not particularly limited, but is preferably in the range of 0.5 μm to 1.5 μm. If the thickness of the adhesive layer is 0.5 μm or more, sufficient adhesive strength can be maintained even if the surface of the adherend is rough.
[0099] <Method of manufacturing laminate> The laminate of the present invention can be produced by laminating the hologram layer 12 onto the resin sheet A (11). The hologram layer 12 can be produced in advance by applying the hologram layer 12 onto the substrate by a known wet coating method, and then drying and removing the solvent component. The hologram layer 12 can also be produced simultaneously with the formation of the concave-convex pattern in the next process. As a wet coating method, roll coating, gravure coating, reverse coating, die coating, screen printing, spray coating, etc. can be used. Using these wet coating methods, the material of the hologram layer (relief layer) 12 is applied to one side of the substrate. As a method for drying the solvent component, known drying methods such as hot air drying, hot roll drying, and infrared irradiation can be used.
[0100] Next, a relief pattern constituting a hologram image is formed by using a metal plate having a desired concave-convex pattern wound around an embossing roll. Here, when a thermosetting resin is used for the hologram layer 12, a concave-convex pattern is formed in the hologram layer 12 by pressing a heated metal plate against the hologram layer 12. On the other hand, when a photocurable resin is used as the hologram layer 12, light is irradiated at the same time as pressing the metal plate to cure the resin, thereby forming a pattern in the hologram layer 12.
[0101] Next, a reflective layer is laminated on the holographic layer 12 on which the concave-convex pattern has been formed. Here, the reflective layer can be formed by, for example, a vapor phase deposition method such as vacuum deposition, sputtering, etc. At this time, the holographic layer 12 may be subjected to a corona treatment in order to improve the adhesion between the holographic layer 12 and the reflective layer. Next, a protective layer and an adhesive layer may be provided on the reflective layer, if necessary.
[0102] Furthermore, when the hologram layer 102 has a substrate, the substrate and resin sheet A may be bonded by press molding or the like. The press molding may be performed only on the substrate of the hologram layer with substrate and resin sheet A, or may be performed simultaneously with bonding of resin sheet B after laminating resin sheet B. The press molding can be performed at a temperature of 160° C. or less under the same press conditions as those described below. In addition, in the case of manufacturing a hologram layer with a substrate, a substrate in place of the resin sheet A is prepared, and a hologram layer is formed on the substrate.
[0103] The laminate in which the hologram layer is formed on the resin sheet A by the above method is laminated so that the surface of the hologram layer other than the resin sheet A side is in contact with the resin sheet B, and press-molded. Here, by using the above resin composition A as the resin sheet A and the resin sheet B, the laminate can be formed by pressing at 160°C or less, preferably 120 to 159°C. In addition, if necessary, the resin sheet A and the resin sheet B can be press-molded by laminating a plurality of sheets. In this way, a laminate having a multilayer structure can be formed, and in particular, by forming a plurality of sheets from the resin composition A, the laminate can be formed at a low temperature of 160°C or less even without an adhesive layer or the like. In addition, in the production of the laminate, an adhesive layer may be provided between the layers as necessary.
[0104] <Card or passport> The laminate is preferably used for cards or passports. As cards, it can be used for various cards such as IC cards, magnetic cards, driver's licenses, residence cards, qualification certificates, employee ID cards, student ID cards, insurance cards, My Number cards, seal registration certificates, vehicle inspection certificates, tag cards, prepaid cards, cash cards, bank cards, credit cards, SIM cards, ETC cards, identification cards, information carrying cards, smart cards, B-CAS cards, and memory cards. The film or resin composition is preferably used for the data page of a passport.
[0105] The card or passport of the present invention (more specifically, the data page of the passport) may include the above-mentioned present film (laminate). The card or passport is usually composed of multiple resin films, at least one of which is preferably the present film. The card or passport may include a core sheet. In addition to the core sheet, the card or passport may include at least one of a laser marking sheet and an oversheet. The passport or card may be manufactured by subjecting the laminate of the present invention to punching processing, etc., or may be manufactured by overlapping the laminate of the present invention and a sheet other than the laminate of the present invention, pressing and heat fusing them, and then subjecting them to punching processing, etc. Also, instead of heat fusing, the sheets may be bonded to each other using an appropriate adhesive, etc.
[0106] When resin sheet A or resin sheet B does not contain an inorganic filler or contains an inorganic filler in an amount that does not impair transparency, resin sheet A or resin sheet B may not contain a color former in one embodiment, but it is also preferable for the resin sheet A or resin sheet B to contain a color former. In an embodiment in which a color former is not contained, resin sheet A or resin sheet B is used as an oversheet, and in an embodiment in which a color former is contained, resin sheet A or resin sheet B can be used as a laser marking sheet. As described below, when a core sheet is provided on the other side of the hologram layer, it is preferable that the oversheet or laser marking sheet is positioned outside the core layer (i.e., farther from the hologram layer) on the other side of the hologram layer.
[0107] On the other hand, resin sheet A or resin sheet B may be made of a resin composition containing an inorganic filler in an amount of 5 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the resin component, but in this embodiment, resin sheet A or resin sheet B is preferably used as a core sheet. In addition, in one embodiment, when there are multiple resin sheets B, the sheet B closest to the hologram layer among the multiple resin sheets B may be made of a resin composition B containing 5 parts by mass or more and 90 parts by mass or less of an inorganic filler relative to 100 parts by mass of the resin component as described above. In this embodiment, the more preferable range of the content of the inorganic filler is as described above.
[0108] Furthermore, on the other side of the hologram layer, the resin sheet B that is positioned outermost, or if a core sheet is provided, the resin sheet B outer than the core sheet may contain a color former as described above to form a laser marking layer, or may contain no inorganic filler, or may contain an inorganic filler in an amount that does not inhibit transparency but does not contain a color former to form an oversheet. In one embodiment, when a plurality of resin sheets B are provided, the sheet B closest to the hologram layer among the plurality of resin sheets B may be made of a resin composition B containing 5 parts by mass or more and 90 parts by mass or less of an inorganic filler relative to 100 parts by mass of the resin component as described above. In this embodiment, the more preferable range of the content of the inorganic filler is as described above.
[0109] Examples of embodiments of the laminate used in the construction of a card or passport in the present invention include resin sheet A / hologram layer / resin sheet B / resin sheet B, resin sheet A / hologram layer / resin sheet B / resin sheet B / resin sheet B (embodiment of FIG. 1), resin sheet A / adhesive layer / hologram layer / resin sheet B / resin sheet B, resin sheet A / hologram layer / adhesive layer / resin sheet B / resin sheet B, resin sheet A / adhesive layer / hologram layer / adhesive layer / resin sheet B / resin sheet B, etc. In addition, the present invention is not limited to the above configuration, and when the laminate is used for a card, passport, etc., another layer may be laminated. In addition, layers other than the above-mentioned resin sheet A, resin sheet B, hologram layer, and adhesive layer may be laminated.
[0110] 2(a), the card is preferably a card 20A having a laser marking sheet 1 and a core sheet 2, with the laser marking sheet 1 on one or both surfaces of the core sheet 2. A hologram layer 102 is provided between the laser marking sheet 1 and the core sheet 2. 3(b), card 20B is also preferred, which further includes an oversheet 4, and which is further laminated as a protective layer on the outside of laser marking sheet 1. The laser marking sheet may be omitted, and the card may be, for example, card 20C, which includes a core sheet 2 and an oversheet 4 as a protective layer on one or both surfaces of core sheet 2, as shown in FIG. Furthermore, the card may have a hologram layer 102 between the laser marking sheet 1 and the oversheet 4, as shown in FIG. 3(b)-1, or may have a hologram layer 102 between the laser marking sheet 1 and the core sheet 2, as shown in FIG. 3(b)-2. Although Figure 3 shows an embodiment in which a laser marking sheet 1, an over sheet 4, or both are provided on both sides of the core sheet 2, a laser marking sheet 1, an over sheet 4, or both may be provided on only one side of the core sheet 2. In addition, in each of the cards 20A to 20C, the layer structures provided on both sides of the core sheet 2 are the same, but they may be different on each side. For example, the laser marking sheet 1 and the oversheet 4 may be provided in this order on one side of the core sheet 2, and only the oversheet 4 may be provided on the other side of the core sheet 2.
[0111] 5(a), a passport is preferably a passport 10A that includes a hinge sheet 3 and a core sheet 2 provided on each side of the hinge sheet 3, with a laser marking sheet 1 laminated on one or both of the outer sides of the core sheet 2. A hologram layer 102 is provided between the laser marking sheet 1 and the core sheet 2. Also preferred is a passport 10B, as shown in Fig. 6(b), which includes an oversheet 4 and is further laminated as a protective layer on the outer side of the laser marking sheet 1. The laser marking sheet may be omitted, and the passport may be a passport 10C, as shown in Fig. 7(c), which includes a hinge sheet 3, a core sheet 2 provided on each side of the hinge sheet 3, and an oversheet 4 as a protective layer on one or both outer sides of the core sheet 2. In this case, a hologram layer 102 is provided between the core sheet 2 and the oversheet 4.
[0112] Furthermore, the passport may have a hologram layer 102 between the laser marking sheet 1 and the core sheet 2, as shown in Figure 6(b)-1, or may have a hologram layer 102 between the laser marking sheet 1 and the oversheet 4, as shown in Figure 6(b)-2. Although Figure 6 shows an embodiment in which the laser marking sheet 1, the over sheet 4, or both are provided on either outer side of the core sheet 2, the laser marking sheet 1, the over sheet 4, or both may be provided on only one outer side of the core sheet 2. In each of the passports 10A to 10C, the layer structures provided on the outer sides of the core sheet 2 are the same, but may be different from each other. For example, the laser marking sheet 1 and the over sheet 4 may be provided in this order on one outer side of the core sheet 2, and only the over sheet 4 may be provided on the other outer side of the core sheet 2.
[0113] In the passports shown in Figures 5(a), 6(b) and 7(c), the core sheets 2, 2 are arranged to sandwich the hinge sheet 3, but this is not particularly limited, and the core sheets do not need to be arranged to sandwich the hinge sheet, and there may be only one core sheet. Also, the core sheet may be formed by stacking multiple core sheets without sandwiching a hinge sheet. Also, the hinge sheet 3 does not need to be in contact with the core sheet, and may be arranged in any position that is not in contact with the core sheet. Instead of being between the core sheets, the hinge sheet may be disposed, for example, but not limited to, between the core sheet and the over sheet, between the core sheet and the laser marking sheet, between the laser marking sheet and the over sheet, etc.
[0114] In the card or passport, the core sheet is preferably a resin film using polycarbonate resin, polyester resin, or a mixture thereof as a resin component, and preferably contains a filler. The core sheet may be a laminate of a plurality of core sheets. The thickness of each core sheet is preferably about 50 to 700 μm. Each core sheet may be a printing sheet on which fixed information is printed, an inlet sheet having a hollow portion for accommodating an inlet such as an IC chip or an antenna, or a concealment sheet for concealing an inlet. Furthermore, an adhesive sheet or the like may be appropriately placed between a pair of adjacent core sheets, and the pair of adjacent core sheets may be bonded together by the adhesive sheet. Each core sheet may be made of a single-layer film or a laminated film having two or more resin layers. The adhesive sheet may be provided between the core sheet and an oversheet or a laser marking sheet.
[0115] The laser marking sheet is preferably a resin film that uses polycarbonate resin, polyester resin, or a mixture of these as the resin component. The laser marking sheet is a sheet on which personal information, etc. is printed by laser printing. The personal information is information for identifying the individual of the passport or card holder, such as the individual's name, personal ID, card number, etc. The laser marking sheet may be formed from a resin film, and the resin film may be a single-layer film or a laminated film having two or more resin layers. The laser marking sheet preferably includes a resin layer containing a laser coloring agent, and in the case of a single-layer film, the single-layer resin layer may contain a laser coloring agent. In the case of a laminated film, the laser marking sheet may have a structure in which a surface layer is provided on both sides of a middle layer, and the middle layer may contain a laser coloring agent. The laser marking sheet is typically a transparent film. The thickness of the laser marking sheet is not particularly limited, but is, for example, about 5 to 400 μm, and preferably 10 to 300 μm.
[0116] An oversheet generally constitutes the outermost layer of the data page of a card or passport, and protects the card or passport. When the oversheet is placed on the outside of the laser marking sheet as shown in Fig. 3(b) and Fig. 6(b), it can suppress so-called "blistering", in which the laser-printed portion foams due to irradiation with laser light. There is no particular limit to the resin used for the oversheet, but examples thereof include polycarbonate resins, polyester resins, and mixtures thereof. There is no particular limit to the thickness of the oversheet, but it is, for example, about 5 to 400 µm, and preferably 10 to 300 µm.
[0117] The hinge sheet in a passport is a sheet that plays a role in firmly binding the data page together with the cover of the passport and other visa sheets, etc. Any known hinge sheet can be used, and may be a resin sheet made of a thermoplastic resin or a thermoplastic elastomer, such as a thermoplastic polyester resin, a thermoplastic polyester elastomer, a thermoplastic polyamide resin, a thermoplastic polyamide elastomer, a thermoplastic polyurethane resin, or a thermoplastic polyurethane elastomer, or may be made of a woven fabric, a knitted fabric, or a nonwoven fabric, or may be a composite material of a woven fabric, a knitted fabric, or a nonwoven fabric with a thermoplastic resin or a thermoplastic elastomer.
[0118] In a card or passport, the resin films used in the core sheet, the laser marking sheet, and the oversheet may be composed of the present film as described above, but as long as the card or passport has at least one of the present films, a resin film other than the present film may be used. Here, it is preferable that the present film is used in at least the core sheet of the card or passport. In addition, when the core sheet is composed of multiple core sheets, at least one of the multiple core sheets may be composed of this film, or all of the core sheets may be composed of this film. In addition, when multiple laser marking sheets and multiple over sheets are provided, at least one of the multiple sheets may be composed of this film, or all of the sheets may be composed of this film. EXAMPLES
[0119] Examples and comparative examples are shown below, but the present invention is not limited by these in any way.
[0120] The method for measuring the glass transition temperature of a resin is as follows. (glass transition temperature) Using a differential scanning calorimeter "Pyris1 DSC" (manufactured by PerkinElmer), the glass transition temperature was measured in accordance with JIS K7121:2012 by increasing the temperature from 30°C to 200°C at a rate of 20°C / min, decreasing the temperature to 30°C at a rate of 20°C / min, and then increasing the temperature again to 200°C at a rate of 20°C / min. The glass transition temperature was determined based on the midpoint glass transition temperature (Tmg).
[0121] The films obtained in the examples and comparative examples were evaluated in the following manner. (Adhesion to hologram layer (substitute evaluation)) The resin sheets obtained in the Examples and Comparative Examples were laminated to a hologram layer substitute (acrylic resin sheet: Acryplene HBS006H manufactured by Mitsubishi Chemical Corporation) by hot pressing. The adhesion was evaluated according to the following criteria. (judgment criteria) ◎: Heat press temperature is 140℃, and adhesion is particularly good. Good: Good adhesion at a heat press temperature of 140°C. △: Good adhesion at a heat press temperature of 170°C.
[0122] (Process reduction effect) In the manufacturing process of the hologram layer, evaluation was carried out according to the following criteria. (judgment criteria) ◎: No peeling process is required, so pressing can be done in one go. ○: No peeling process is included, but pressing is required two or more times for alignment, etc. ×: A peeling step is included and pressing is required two or more times.
[0123] The raw materials used in the examples and comparative examples are as follows. (resin) ISP: A polycarbonate resin obtained by melt polymerization using isosorbide and 1,4-cyclohexanedimethanol as dihydroxy compounds, with the structural unit derived from isosorbide:structural unit derived from 1,4-cyclohexanedimethanol = 50:50 (molar ratio); glass transition temperature: 98℃ PC: Bisphenol A homopolycarbonate resin (interfacial polymerization method), glass transition temperature: 159℃ (filling material) Filling material: Titanium oxide (rutile type, refractive index 2.7)
[0124] [Example 1] Resin composition A (ISP) was charged into a twin-screw extruder and kneaded, and the resin composition was extruded at 230° C. using the twin-screw extruder to obtain a resin sheet A having a thickness of 100 μm. Resin composition A and titanium oxide as a metal oxide were charged into a twin-screw extruder and kneaded, and the resin composition was extruded at 230° C. using the twin-screw extruder to obtain a resin sheet B having a thickness of 100 μm. Resin sheet A / hologram layer / resin sheet B were bonded together at a heat press temperature of 140°C.
[0125] [Example 2] A laminate was obtained in the same manner as in Example 1, except that the hologram layer in Example 1 was changed to PET with a polyester (PES) adhesive layer.
[0126] [Comparative Example 1] The PET film and the hologram layer were bonded together. The hologram layer was heat-pressed with resin sheet B at 170° C., and then the PET film was peeled off from the hologram layer.
[0127] [Reference example] A resin sheet was obtained in the same manner as in Example 1, except that the resin compositions A and B in the example were changed to polycarbonate (PC). In the case of polycarbonate, the resin composition was extruded at 270°C.
[0128] [Table 1] [Industrial Applicability]
[0129] According to the laminate of the present invention, since it can be press molded at a temperature of 160°C or less, there is no distortion or elongation in the hologram layer. Therefore, it is an industrially valuable technology since it is possible to obtain cards, passports, etc. with excellent appearance. In addition, since the lamination of the hologram is not produced by a transfer method using a transfer foil, a base film such as a PET film is not required, no waste material is generated, and the production process can be simplified, making it an industrially valuable technology as a production method. [Explanation of symbols]
[0130] 1 Laser marking sheet 2 Core Sheet 3 Hinge Sheet 4 Overseat 20A, 20B, 20C Cards 10A, 10B, 10C Passport 100 Laminate 101 Overlay layer (resin sheet A) 102 Hologram Layer 103, 104 Core layer 105 Overlay layer (resin sheet B)
Claims
1. A laminate in which a resin sheet A is laminated on one side of a hologram layer, the resin sheet A being made of a resin composition A containing a polycarbonate resin (A) having a structural unit (A1) derived from a dihydroxy compound having a moiety represented by the following formula (1) as part of its structure: 【Chemistry 1】 However, the moiety represented by the formula (1) is -CH 2 Except when it is part of -O-H.
2. 2. The laminate according to claim 1, wherein a resin sheet B is laminated on the other surface of the hologram layer, the resin sheet B being made of a resin composition B containing a polycarbonate resin.
3. The laminate according to claim 2, wherein the resin composition B is a resin composition A containing a polycarbonate resin (A) having a structural unit (A1) derived from a dihydroxy compound having a moiety represented by the following formula (1) as a part of its structure: 【Chemistry 2】 However, the moiety represented by the formula (1) is -CH 2 Except when it is part of -O-H.
4. The laminate according to claim 1 , wherein the resin composition A constituting the resin sheet A contains an inorganic filler.
5. The laminate according to claim 2 , wherein the resin composition B constituting the resin sheet B contains an inorganic filler.
6. The laminate according to claim 4 or 5, wherein the inorganic filler is a metal oxide.
7. The laminate according to claim 4 or 5, wherein the inorganic filler is titanium oxide.
8. The laminate according to claim 4 or 5, wherein the content of the inorganic filler is 5 parts by mass or more and 90 parts by mass or less per 100 parts by mass of the resin component in each of the resin compositions A and B.
9. The laminate according to claim 2 , wherein the resin composition B constituting the resin sheet B contains a color former.
10. The laminate according to claim 9 , wherein the content of the color former is 0.01 parts by mass or more per 100 parts by mass of the resin component in the resin composition B.
11. 4. The laminate according to claim 1, wherein the polycarbonate resin (A) contains 30 mol % or more of the structural unit (A1) in structural units derived from a dihydroxy compound.
12. 4. The laminate according to claim 1, wherein the polycarbonate resin (A) contains the structural unit (A1) in an amount of 80 mol % or less in structural units derived from a dihydroxy compound.
13. 4. The laminate according to claim 1, wherein the polycarbonate resin (A) further comprises a structural unit (A2) which is derived from at least one dihydroxy compound selected from the group consisting of an aliphatic dihydroxy compound and an alicyclic dihydroxy compound and is a structural unit other than the structural unit (A1).
14. 3. The laminate according to claim 1, wherein the holographic layer is of a relief type.
15. A card or passport comprising the laminate according to claim 1 or 2.
16. The method for producing a laminate according to claim 1 or 2, wherein the hologram layer and at least one of the resin sheet A and the resin sheet B are pressed at 160° C. or lower.
Citation Information
Patent Citations
Hologram transfer foil
JP2019214172A